Proyecto de factibilidad para la implementación de una empresa productora de guayaba enlatada y su comercialización en las provincias de Loja y Zamora Chinchipe. - Ortega Astudillo, Gabriela (2010)
The implementation of an enterprise of production and marketing of canned guava will be located in the county seat of Zamora Canton aims to provide a new product on the market that satisfies the tastes and preferences of future customers. In the first part of the work there was realized the introduction of the work in which there is done an analysis of the local economy, later one proposes the review of literature used in the investigation, in the materials and methods appear the methods and technologies used in the scientific investigation, in the market research applied 393 surveys to the plaintiffs of Loja's province and 399 for the province of Zamora, being an unsatisfied demand in both provinces of 256.961 tins of 250 gr., while the competition offers an average of 46.461 tins of 250 gr., the unsatisfied demand of this product shows that there is viable the implementation of this type of company, with a capacity installed to produce 82.896 jars of 250 grams, being in use a capacity installed to produce 82.896 jars of 250 grams, being in use a capacity in the first year of functioning of 80 %, in the second year 85 % and from the third year 90 % of the installed capacity. It will form a limited liability company, which will have two members, who financed a total of $ 17.124,43 and the request for a loan for an amount of $ 10,000.00. According to the financial analysis carried out concluded that the project is feasible if implemented, due to existing demand and a reasonable profit margin will produce a safe return for investors, more than the legal feasibility that allows the formation of these companies, ensuring their market positioning. The conclusions and recommendations which was reached soon after completion of the research are presented in the respective numeral.